2023
DOI: 10.1002/oby.23796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐nutritive sweetened beverages versus water after a 12‐week weight‐loss program: A randomized controlled trial

Abstract: Objective: The aim of this study was to compare non-nutritive sweetened (NNS) beverages versus water for weight loss after a 12-week behavioral weightmanagement program.Methods: This is an ongoing, 2-year, parallel-group, open-label, controlled equivalence trial; week-12 data are reported. Adults with BMI of 27 to 35 kg/m 2 who regularly drank cold beverages were randomized 1:1 to intention-to-treat water or NNS beverages while undergoing a weekly 12-week group behavioral weightmanagement program. Weight chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The full eligibility criteria for the SWITCH trial have been reported previously [ 16 ]. Briefly, healthy adults aged 18–65 years with a BMI of 27–35 kg/m 2 who regularly consumed >3 cold beverages per week (water, or <2 l per day of NNS or sugar-sweetened beverage) from within a 50-mile radius of the county of Merseyside, England (of which Liverpool is the principal city) were included.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The full eligibility criteria for the SWITCH trial have been reported previously [ 16 ]. Briefly, healthy adults aged 18–65 years with a BMI of 27–35 kg/m 2 who regularly consumed >3 cold beverages per week (water, or <2 l per day of NNS or sugar-sweetened beverage) from within a 50-mile radius of the county of Merseyside, England (of which Liverpool is the principal city) were included.…”
Section: Methodsmentioning
confidence: 99%
“…Full details on protocol amendments and approval, including ethical approval, have been reported elsewhere [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations